Evaluation of CA-125 and soluble CD-23 in patients with pelvic endometriosis: a case-control study - Ramos,Ivana Maria de Luna (2012)
OBJECTIVE: To evaluate serum concentrations of CA-125 and soluble CD-23 and to correlate them with clinical symptoms, localization and stage of pelvic endometriosis and histological classification of the disease. METHODS: Blood samples were collected from 44 women with endometriosis and 58 without endometriosis, during the first three days (1st sample) and during the 7th, 8th and 9th day (2nd sample) of the menstrual cycle. Measurements of CA-125 and soluble CD-23 were performed by ELISA. Mann-Whitney U test was used for age, pain evaluations (visual analog scale) and biomarkers concentrations. RESULTS: Serum levels of CA125 were higher in endometriosis patients when compared to the control group during both periods of the menstrual cycle evaluated in the study. This marker was also elevated in women with chronic pelvic pain, deep dyspareunia (2nd sample), dysmenorrhea (both samples) and painful defecation during the menstrual flow (2nd sample). CA-125 concentration was higher in advanced stages of the disease in both samples and also in women with ovarian endometrioma. Concerning CD-23, no statistically significant differences were observed between groups. CONCLUSION: The concentrations of CA-125 were higher in patients with endometriosis than in patients without the disease. No significantly differences were observed for soluble CD-23 levels between groups.